Grammatical Knowledge: Does It Affect Listening Comprehension? - Desi Surlitasari Dewi (English Department, University of Riau Kepulauan, Batam,Indonesia, 2017)
Understanding an utterance is one of the goal in listening comprehension. An utterance consists of words and clauses that has a structure to bond them. It is interesting to find out whether the student’s knowledge of grammatical structure has a role in their listening comprehension. Thus, the aim of this research was to find out whether any effect of grammatical knowledge towards student’s listening comprehension. The data of student’s listening comprehension were administered through a listening test of TOEFL by Phillips. While, the data for student’s grammatical knowledge were assessed by grammar test by Azar. The participants of this study were eighty students of English Department Universitas Riau kepulauan taken by purposive sampling. Then, tukey test was used to analyze the data. The finding showed that student’s grammatical knowledge had an effect on their listening comprehension. Thus, it is recommended for test takers not only to learn listening skills such as pronunciation, or vocabulary, but it is also important to master grammatical knowledge such as negative with comparative which have superlative meaning, double negative expression meaning statement positive, knowing the subjects in passive sentences, multiple nouns, and others to be able to increase listening comprehension.